Six scooter operators, six maps: Spatial coverage and regulation of micromobility in Vienna, Austria. Issue 2 (June 2020) - Moran, Marcel E.; Laa, Barbara; Emberger, Guenter
Highlights: Over the summer of 2019, the geofences (virtual geographic boundaries) of six scootersharing schemes in Vienna were analyzed to determine their spatial variance, rate of change, and no-parking zones. The resulting spatial dynamics of scootersharing demonstrate overlapping, but non-identical geofences (which change often), biases in which neighborhoods are included, and diverging interpretation of municipal regulations. Overall, scootersharing geofences and no-parking zones analyzed illustrate significant downsides (including access gaps) for riders and municipalities. Policy recommendations are provided for cities to more explicitly oversee the spatial footprint of new mobility services, and incentivize more equitable coverage. Abstract: Background and objective: Electric scooters in shared schemes bring benefits to users in the form of on-demand, point-to-point transport, but pose new challenges for municipal regulation, including access issues related to their geographic availability. The size and position of the geographic service areas, or 'geofences' of scootersharing schemes determine where users can locate vehicles to begin a ride and park them to conclude one. The purpose of this study is to understand the spatial variance in scooter geofences in Vienna, Austria and how those differences relate to existing municipal regulations, as well as what may be learned from this case for the benefit of cities worldwide which are also grappling with this mobility trend. Methods: Over the course of one summer, all scooter geofences and no-parking zones for the six operators in Vienna were tracked via smartphone applications and manually digitized on a weekly basis. This enables spatial analyses across scooter operators, and sheds light on such issues as differences in geofence size, shape, and placement, no-parking zone categories, and the frequency of geofence modification. Results: Across the six scooter operators in Vienna, geofence coverage differed sharply over this time period, as did where scooter parking was prohibited (via no-parking zones). Categorization of no-parking zones indicate that the bulk are located around parks, pedestrianized corridors, and cultural institutions. Moreover, all six scooter operators modified their geofences during the course of this study (adding neighborhoods and removing others), which took place without any type of municipal approval or standardized disclosure to users. Four operators expanded their geofences, while two contracted them. Conclusion: These observations combine to establish a scootersharing profile of Vienna (matching regulations against spatial outcomes) that can serve as the basis for future comparison cases worldwide. Moreover, they indicate that there is likely a role for the public sector to provide oversight over the spatial dynamics of scootersharing, such as by establishing incentives to ensure outlying and/or transit-poor neighborhoods are not excluded, and via basic disclosure of geofences for the benefit of riders, transit planners, and trip-planning or wayfinding applications.